Home » Past Questions » Mathematics » Simplify 2\(\frac{5}{12}\) - 1\(\frac{7}{8}\) x \(\frac{6}{5}\)

Simplify 2\(\frac{5}{12}\) - 1\(\frac{7}{8}\) x \(\frac{6}{5}\)


Question

Simplify 2\(\frac{5}{12}\) - 1\(\frac{7}{8}\) x \(\frac{6}{5}\)

Options

A)
\(\frac{1}{6}\)
B)
\(\frac{13}{20}\)
C)
\(\frac{11}{30}\)
D)
\(\frac{9}{4}\)
E)
\(\frac{5}{3}\)

The correct answer is A.

Explanation:

2\(\frac{5}{12}\) - 1\(\frac{7}{8}\) x \(\frac{6}{5}\) = \(\frac{29}{12}\) - \(\frac{15}{8}\) x \(\frac{6}{5}\)
= \(\frac{29}{12}\) - \(\frac{9}{4}\)
= \(\frac{29 - 27}{12}\)
= \(\frac{2}{12}\)
= \(\frac{1}{6}\)

More Past Questions:


Dicussion (1)

  • 2\(\frac{5}{12}\) - 1\(\frac{7}{8}\) x \(\frac{6}{5}\) = \(\frac{29}{12}\) - \(\frac{15}{8}\) x \(\frac{6}{5}\)
    = \(\frac{29}{12}\) - \(\frac{9}{4}\)
    = \(\frac{29 - 27}{12}\)
    = \(\frac{2}{12}\)
    = \(\frac{1}{6}\)

    Reply
    Like